Case Report: Novel RPGRIP1L Gene Mutations Identified by Whole Exome Sequencing in a Patient With Multiple Primary Tumors - Guo, Jiani; Yang, Yu; Ji, Zhuqing; Yao, Mengchu; Xia, Xiaotian; Sha, Xiaofeng; Huang, Mingde (Frontiers in Genetics, 2021)
A 78 years old Chinese woman with five different cancer types and family history of malignancy participated in our project. The patient’s pancreatic adenocarcinoma and gingival squamous carcinoma tissues were obtained and sequenced by Whole Exome Sequencing, which had found 20 mutation sites in 6 candidate genes. Sanger Sequencing were applied for further validation. The result had verified 6 mutations of three genes, OBSCN, TTN, and RPGRIP1L, in at least one cancer type. Further analysis of protein expression verified by Immunohistochemistry, and mRNA expression using TCGA database demonstrated that RPGRIP1L was highly expressed in several cancer types, especially in pancreatic adenocarcinoma, and correlated with patient survival and sensitivity to paclitaxel, probably through TGF-β signaling pathway. The newly identified somatic mutations of RPGRIP1L gene might contribute to the pathogenesis of the patients. Protein conformation simulation demonstrated that the alterations had made the binding pocket of position 708 to change from concave to convex, which could restrict the contraction and extension, and interfere with the physiological function of protein. Further studies are required to determine the implication of RPGRIP1L in the family and multiple primary tumors.